Regard sur la santé des personnes noires et le racisme anti-Noirs dans les systèmes de santé au Canada - Patrick, Kirsten (CMAJ : Canadian Medical Association Journal, 2023)

“It’s Not Just about Work and Living Conditions”: The Underestimation of the COVID-19 Pandemic for Black Canadian Women - Knight, Melanie; Ferguson, Renée Nichole; Reece, Rai (Social Sciences, 2021)
The COVID-19 pandemic has increasingly been deﬁned as the shecession for its disproportionate debilitating impact on women. Despite this gendered analysis, a number of health activists have called on governments to account for the experiences of Black communities as they are disproportionately suffering the effects of this pandemic. In the media’s address of the impact of the pandemic, we ask, what experiences are represented in news stories and are Black women present in these representations. Performing a content analysis of 108 news articles, a reading of media discourses through a racial lens reveals a homogenization of women’s experiences and an absence of the Black experience. In the small number of news stories that do focus on Black women, we see that the health disparities are not simply the result of precarious work and living conditions, but also the struggle against anti-Black racism on multiple fronts. In critiquing, however, we also bring forth the small number of news stories on the Black experience that speak to the desire and hope that can thrive outside of white supremacist structures.

Qui est Noir ? Il est urgent de préciser la définition de la population noire dans la réalisation de recherches sur la santé au Canada - Cénat, Jude Mary (CMAJ : Canadian Medical Association Journal, 2022)